Спосіб зниження пиловиділення при проведенні вугільних виробок вибухом - Савельєв, Д. В.; Столбченко, О. В. (НТУ ДП, 2022)
У роботі проведені дослідження з розробки конструкції заряду з використанням пластичної суміші в якості набійки, яка розширюється і твердіє. Забезпечення перерозподілу і зниження питомого імпульсу в зоні інтенсивного подрібнення породи вибухом дозволяє управляти кусковатістю гірської маси і забезпечує загальне зниження запиленості рудникової атмосфери.

In the work researches on development of a design of a charge with use of plastic mix as a packing which expands and hardens are carried out. Ensuring the redistribution and reduction of the specific impulse in the zone of intensive crushing of the rock by the explosion allows you to control the lumpiness of the rock mass and provides an overall reduction in dust in the mine atmosphere.
Method of reducing dust emissions during coal products by explosion
Keywords: вибухові роботи; твердіюча набійка; дрібнодисперсний пил; blasting works; hardening punch; fine dust; working conditions